(untitled) - Brenner, Gail Abel (Indianapolis, Ind, 2003)
This resource provides clear explanations of some 3,500 American idioms, with notes on grammar and usage and many examples. Idioms are organized by common themes and concepts. There is an appendix on differences between American and British idioms
Keywords: English language,Americanisms; Idioms; United States